Una nova proposta d'identificació de l'«alqueria mia per nom Xilvella» de la crònica de Ramon Muntaner: les Cases de Bàrcena, al nord de la ciutat de València. - BAYDAL SALA, VICENT; ESQUILACHE MARTÍ, FERRAN (Scripta, 2020)
"My farm called Xilvella" where Ramon Muntaner's chronicle begins has been traditionally identified with the current municipality of Xirivella, south of the city of Valencia, although at the same time doubts have always remained, given the lack of documentary evidence to confirm it and the existence of some to disprove it. In this article we propose another location for the farm of Ramon Muntaner, that is, the rural area that appears in the Llibre del Repartiment of James I as Xilvella al-Xarquia, in the current term of Les Cases de Bàrcena, a district north of the same city of Valencia. Several documentary and landscape indications point this out.